CRISIS COMMUNICATION THROUGH GOVERNMENT SOCIAL MEDIA (@BTN_GN_RINJANI) IN HANDLING THE BRAZILIAN TOURIST ACCIDENT ON MOUNT RINJANI - Nurjanah, Anna; Hesti, Sri; Aliagan, Isiaka Zubair (ASPIKOM Jabodetabek Region, 2025)
This study examines the role of Instagram in governmental crisis communication following the accident involving a Brazilian tourist at Mount Rinjani National Park, Indonesia. Using a qualitative content analysis approach, the research analyzes ten Instagram posts published by the official account @btn_gn_rinjani between June 22 and June 27, 2025. The study integrates Entman’s framing theory and Situational Crisis Communication Theory (SCCT) to assess how crisis narratives, responsibility attribution, and institutional credibility were constructed in a digital environment. The findings reveal a consistent communication pattern characterized by timely informational updates, solution-oriented framing, and empathetic messaging. From a framing perspective, the posts predominantly emphasized problem definition and suggested remedies, while minimizing moral judgment to maintain a neutral institutional stance. Within the SCCT framework, the crisis was positioned within the unintentional (victim) cluster, utilizing a combination of diminish (excuse/justification) and rebuild strategies to mitigate accountability. Additionally, the study highlights the strategic use of inter-agency collaborative content and hashtags as symbolic framing devices that reinforced institutional legitimacy and collective identity. The findings demonstrate that Instagram functioned as a multi-dimensional space for legitimization, emotional management, and reputational protection. This research contributes to the literature on digital crisis communication in tourism by providing empirical evidence from a conservation-based destination involving international stakeholders, concluding that institutionalized digital literacy is a fundamental capability for crisis governance in high-risk environments.